Dialing the glenosphere eccentricity posteriorly to optimize range of motion in reverse shoulder arthroplasty - Stefan Bauer, MD; Arnaud Meylan, MD; Jaad Mahlouly, MD; Wei Shao, MD; William G. Blakeney, MBBS, MSc, MS, FRACS (JSES International)
Background: Friction is the primary cause of notching in reverse shoulder arthroplasty during internal, external rotation (IR/ER), and extension (EXT). To address notching, glenosphere eccentricity (ECC) was introduced. The primary objective of this study was to investigate different positions of glenosphere ECC to determine whether there is an optimal position for impingement-free range of motion. Methods: In this computer model study, 10 female CTs were analyzed and EXT, ER, IR, and adduction simulated (18 models.) A 135° stem with a +10° liner (145°) was combined with a 25-mm standard/or +3-mm lateralized baseplate (BP) and a 36-mm +2-mm eccentric glenosphere in 4 ECC positions (50° posterior; 30° posterior; 30° anterior; 50° anterior) from the reference position 0° neutral (10 models). Additionally, a concentric 39-mm glenosphere was tested (+2 models). A 0° insert, 135° neck shaft angle (NSA), was tested with a 25-mm standard/or +3-mm BP for 3 configurations (30° posterior; neutral; 39 mm; +6 models). Results: Compared to the 0° neutral reference position, 30° posterior dialing improved the mean ER (group 145°: 40° vs. 38°, group 145° + 3: 51° vs. 49°, both P < .0001), and EXT (group 145°: 35° vs. 34°, P = .029, group 145° + 3: 57° vs. 47°, P = .046, but at the expense of IR (group 145°: 83° vs. 87°, group 145° + 3: 87° vs. 91°, both P < .0001). The position 30° anterior increased IR (group 145°: 90° vs. 87°, group 145° + 3: 94° vs. 91°, both P < .0001) at the expense of ER (group 145°: 33° vs. 38°, group 145° + 3: 44° vs. 49°, both P < .0001) and EXT (group 145°: 24° vs. 34°, P = .055, group 145° +3 mm: 39° vs. 47°, P = .0042). For group 145°, 0° neutral was the best position for combined EXT + IR (121°) compared to 30° posterior/30° anterior/39 mm/50° posterior/50° anterior (118°/113°/118°/113°/110°, P < .0001/P = .15/P = .076/P < .0001/P = .074, respectively) and IR + ER (125° vs. 122°/123°/123°/118°/119°/, P < .001/P = .0028/P = .7/P < .0001/P = .0001, respectively). Lateralization, but most effectively a 135° NSA improved combined EXT + IR + ER + adduction (group 145°: 179° vs. group 135°: 243°, group 145° + 3: 215° vs. group 135° + 3: 276°, P = .0019/P = .00019, respectively). The influence of position 0°neutral or 30°posterior became marginal with a 135°NSA. Conclusion: Posterior dialing of the ECC increases EXT and ER but at the expense of IR. Lateralization, but most effectively a 135° NSA, increase impingement-free motion. A larger noneccentric glenosphere on the same BP is a safe all-round solution to prevent ECC positioning outliers.